Analisis Kemampuan Berpikir Kreatif dan Proses Pengembangan Kemampuan Berpikir Kreatif Siswa SMP pada Pembelajaran Biologi - Firdaus, Hilman M.; Widodo, Ari; Rochintaniawati, Diana (Assimilation: Indonesian Journal of Biology Education, 2018)
The aim of this research was to analyse students’ creative thinking ability and the process involved in the development of students’ creative thinking, as well as to examine the differences between male and female students, in order to provide a better understanding of both gender in creative thinking ability. Creative thinking is represented by four indicators; fluency, flexibility, originality, and elaboration. In this research students’ creative thinking was measured by using a Test of Creative Thinking Ability, which consisted of five open-ended questions, while the process of creative thinking development was obeserved throughout the classroom teaching-learning activities, as well as the strategies and approaches implied by the teacher. The result showed student’s creative thinking ability was adequate (59%), in which the students scored the highest number in fluency (71,2%), followed by elaboration (59,5%), originality (58,5%), and flexibility (46,8%). Meanwhile, the process of creative thinking development was considered generally adequate in supporting students’ creative thinking ability, the score of the whole process in each indicators were: fluency (85,7%), flexibility (85,7%), originality (78,5%), elaboration (94,5%). Quantitative data analysis showed a statistically different results of fluency and elaboration between male and female students, while the result in flexibility and originality showed no-significant difference between both gender. Positive response related to students’ perception about their creative thinking ability were obtained using the students’ questionnaire as the instrument. Most of the students had a great perception of ther creative ability, where male students tend to have higher perspective about their creative ability than female students.